MATH SOLVE

4 months ago

Q:
# Match each quadratic function given in factored form with its equivalent standard form listed on the left. f(x) = (x + 2)(x – 6) f(x) = (x – 4)(x + 3) f(x) = (x – 12)(x + 1) f(x) = (x – 3)(x + 4)

Accepted Solution

A:

Step-by-step explanation:Write the standard form for the given factored form of quadratic functions f(x) = (x + 2)(x – 6)to get standard form we multiply the parenthesis using FOIL method[tex]f(x)=(x + 2)(x – 6)= x^2 -6x+2x-12= x^2-4x-12[/tex] f(x) = (x – 4)(x + 3)[tex]f(x)=(x – 4)(x + 3)= x^2 +3x-4x-12= x^2-x-12[/tex] f(x) = (x – 12)(x + 1)[tex]f(x)= (x – 12)(x + 1)=(x^2 +1x-12x-12= x^2-11x-12[/tex] f(x) = (x – 3)(x + 4)[tex]f(x)=(x – 3)(x + 4)= x^2 +4x-3x-12= x^2+x-12[/tex]